Some reflections of Vietnamese and American Cultural values on Vietnamese-American Business Negotiation = Các giá trị văn hóa Việt nam, Hoa kỳ phản ánh trong đàm phán thương mại Việt-Mỹ. M.A Thesis Linguistics: 60 22 15 - Lê, Thị Vân Nga (ĐHNN, 2017)
45 p. + CD-ROM